Analysis of Financial Performance Measurement Sharia Bank Using RGEC and SCnp (Shariah Conformity and Profitability) Model - Saparuddin Siregar; Mutiara Shifa (Journal Research of Social Science, Economics, and Management, 2021)
The problem in this study is how the financial performance problems of BUMN Islamic banks using the RGEC and SCnP models and the comparison of the two methods. This study aims to determine the financial performance of state-owned Islamic banks using the RGEC and SCnP models and to compare the two methods. The type of research that the author uses is quantitative research. Data collection techniques using documentation through financial reports obtained from the official website of PT. BRI Syariah Tbk, PT. BNI Syariah, and PT. Bank Mandiri Syariah. The data analysis technique uses financial ratios and Sharia Conformity and Profitability (SCP) as measured by indicators of sharia conformity and profitability. The results showed that PT. BRI Syariah, Tbk in 2017, 2018, and 2019 based on the RGEC method, respectively, were at a composite rank of 3, while in the SCnP Model, each PT. BRI Syariah, Tbk is in the LLQ, LRQ, and LRQ quadrants. For PT. BNI Syariah in 2017, 2018, and 2019 based on the RGEC method was ranked 2, 2, and 1, respectively, while in the SCnP Model, PT. BNI Syariah is in the ULQ, ULQ, and URQ quadrants. Then PT. Bank Syariah Mandiri in 2017, 2018, and 2019 based on the RGEC method was respectively ranked 2, 2, and 1, while in the SCnP Model, PT. Mandiri Syariah Bank is in the next LLQ, LRQ, and URQ quadrants.